Nuevos hospedantes de Aphelenchoides beáeyi (Christie, 1942) en Cuba - Perez, A.=700 1 Fernandez, E.
(Es, En)
Ilus., 4 ref.
Keywords: JARDINES; APHELENCHOIDES BEáEYI; NEMATODA; DAÑOS A LAS PLANTAS; ESPECIES NUEVAS; CUBA